Salicylic acid alleviates the effects of cadmium and drought stress by regulating water status, ions, and antioxidant defense in Pterocarya fraxinifolia - Torun, Hülya; Cetin, Bilal; Stojnic, Srdjan; Petrík, Peter (Frontiers in Plant Science, 2024)
Pterocarya fraxinifolia (Poiret) Spach (Caucasian wingnut, Juglandaceae) is a relict tree species and little is known about its tolerance to abiotic stress factors, including drought stress and heavy metal toxicity. In addition, salicylic acid (SA) has been shown to have a pivotal role in plant responses to biotic and abiotic stress. Hence, the current study is focused on evaluating the impact of foliar application of SA in mediating Caucasian wingnut physiological and biochemical responses, including growth, relative water content (RWC), osmotic potential (Ψs), quantum yield (Fv/Fm), electrolyte leakage, lipid peroxidation, hydrogen peroxide, and antioxidant enzymes, to cadmium (Cd; 100 µM) and drought stress, as well as their interaction. Moreover, the antioxidant activity (e.g., ascorbate peroxidase, catalase, glutathione reductase, peroxidase, and superoxide dismutase activities) of the stressed trees was investigated. The study was conducted on six-month-old seedlings under controlled environmental conditions in a greenhouse, during three weeks. Leaf length, RWC, Ψs and Fv/Fm were decreased under all treatments, although the effect of drought stress was the most pronounced. An efficient antioxidant defense mechanism was detected in Caucasian wingnut. Moreover, SA-treated Caucasian wingnut plants had lower lipid peroxidation, as one of the indicators of oxidative stress, when compared to non-SA-treated groups, suggesting the tolerance of this plant to Cd stress, drought stress, and the combination of them. Cadmium and drought stress also changed the ion concentrations in Caucasian wingnut, causing excessive accumulation of Cd in leaves. These results highlight the beneficial function of SA in reducing negative effects of Cd and drought stress on Caucasian wingnut plants.